1987
DOI: 10.1063/1.337808
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of GaAs self-aligned refractory-gate metal-semiconductor field-effect transistor (MESFET) integrated circuits

Abstract: GaAs metal-semiconductor field-effect transistors (MESFETs) and other integrated-circuit elements were characterized by including extensive process test sites on wafers with digital logic and memory circuits. A self-aligned, refractory-gate enhancement/depletion (E/D) process was employed which included 47SiF+ channel and source/drain implants, capless arsenic overpressure furnace annealing, WSi0.11 gate metal with in situ sputter cleaning, Ni-Au-Ge ohmic contacts, Si3N4 or SiO2 insulation, and Ni-Au wiring. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Typical intrinsic time delay for such kind of inverter can he lower than I 00 p5 for I i.m gate length devices and the speed-power product below the pJ range (5). By controlling the doping level of the channel it is possible to obtain enhancement or depletion mode transistors.…”
mentioning
confidence: 99%
“…Typical intrinsic time delay for such kind of inverter can he lower than I 00 p5 for I i.m gate length devices and the speed-power product below the pJ range (5). By controlling the doping level of the channel it is possible to obtain enhancement or depletion mode transistors.…”
mentioning
confidence: 99%
“…Then, the contact was annealed by a laser beam at temperatures just at the NiGe melting point. The contact had good thermal stability during subsequent annealing at 350 8C for 6 h. However, this fabrication process was not compatible with the conventional GaAs metal semiconductor ®eld-effect transistor (MESFET) process [94]. In addition, the thermal stability required for VLSI devices was at temperatures of about 400 8C for 2 h.…”
Section: Necessity For Development Of Non-gold Ohmic Contacts Materialsmentioning
confidence: 99%
“…EL2 level has been shown to be the major electron trap in GaAs by various experiments (1)(2)(3)(4)(5)(6). Earlier studies have shown that this level is closely related to the dislocation density and causes fluctuations in the MESFET threshold voltage across the wafer (7-9).…”
Section: Introductionmentioning
confidence: 99%
“…Sputtered refractory gate materials are commonly used in the fabrication of submicron self-aligned MESFETs (1)(2)(3). "However, the sputter deposition and the subsequent reactive ion etching (RIE) of the gate can result in both damage and contamination of the GaAs surface (4).…”
mentioning
confidence: 99%
See 1 more Smart Citation